The Association Between Folate and Alzheimer's Disease: A Systematic Review and Meta-Analysis - Zhang, Xiaohong; Bao, Guangyi; Liu, Debiao; Yang, Yu; Li, Xuezhi; Cai, Gaomei; Liu, Yan; Wu, Yili (Frontiers in Neuroscience, 2021)
Alzheimer’s disease (AD) is the most common type of neurodegenerative diseases leading to dementia in the elderly. Increasing evidence indicates that folate plays an important role in the pathogenesis of AD. To investigate the role of folate deficiency/possible deficiency in the risk of AD and the benefical effect of sufficient folate intake on the prevention of AD, a systematic review and meta-analysis were performed. Web of Science, PubMed, CENTRAL, EBSCO, CNKI, CQVIP and Wanfang databases were searched. The analysis of cross-sectional studies showed that the standardized mean difference (SMD) was −0.60 (95% confidence interval (CI): −0.65, −0.55), indicating plasma/serum folate level is lower in AD patients than that in controls. Moreover, the combined odd ratio (OR) of case-control studies was 0.96 (95% CI: 0.93, 0.99), while the combined OR were 0.86 (95% CI: 0.46, 1.26) and 1.94 (95% CI: 1.02, 2.86) in populations with normal level of folate (≥13.5 nmol/L) and folate deficientcy/possible deficiency (<13.5 nmol/L), respectively. In addition, the risk ratio (RR) of cohort studies were 1.88 (95% CI: 1.20, 2.57) in populations with folate deficientcy/possible deficiency. Furthermore, when the intake of folate was equal to or higher than recommended daily allowance, the combined RR and hazard ratio (HR) were 0.44 (95% CI: 0.18, 0.71) and 0.76 (95% CI: 0.52, 0.99), respectively. These results indicate that folate deficientcy/possible deficiency increases the risk for AD, while sufficient intake of folate is a protective factor against AD.